RAC1 Involves in the Radioresistance by Mediating Epithelial-Mesenchymal Transition in Lung Cancer - Tan, Shiming; Yi, Pin; Wang, Heran; Xia, Longzheng; Han, Yaqian; Wang, Hui; Zeng, Biao; Tang, Lu; Pan, Qing; Tian, Yutong; Rao, Shan; Oyang, Linda; et al. (Frontiers in Oncology, 2020)
Radiation therapy is a common and acceptable approach for lung cancer. Although the benefit of ionizing radiation (IR) is well-established, cancer cells can still survive via pro-survival and metastasis signaling pathways. Ras related C3 botulinum toxin substrate1 (RAC1), a member of Rho family GTPases, plays important roles in cell migration and survival. In the present study, we investigated the effects of RAC1 on the survival of lung cancer cells treated with irradiation. The results showed RAC1 is overexpressed in lung cancer cells and promoted cell proliferation and survival. Furthermore, IR induced RAC1 expression and activity via the activation of PI3K/AKT signaling pathway, and then enhancing cell proliferation, survival, migration and metastasis and increasing levels of epithelial-to-mesenchymal transition (EMT) markers, which facilitated the cell survival and invasive phenotypes. In addition, overexpression of RAC1 attenuated the efficacy of irradiation, while inhibition of RAC1 enhanced sensitivity of irradiation in xenograft tumors in vivo. Collectively, we further found that RAC1 enhanced radioresistance by promoting EMT via targeting the PAK1-LIMK1-Cofilins signaling in lung cancer. Our finding provides the evidences to explore RAC1 as a therapeutic target for radioresistant lung cancer cells.